2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32803
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Computing Identity and Persistence Across Multiple Groups Using Structural Equation Modeling

Abstract: He is a computer scientist and a business strategist with over 10 years of experience in academia and industry. His research interests span the fields of Computing Education, Software Engineering Management, Data Analysis, Robotics, and Artificial Intelligence. He has published more than 30 papers at numerous journals and conferences in robotics, software engineering, and computer science education. He has garnered multiple international awards in innovation including the third place in Robocup world competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Previous scholarship has demonstrated that the development of a strong STEM identity positively impacts STEM persistence and intention to persist (e.g., Brickhouse et al, 2000; Carlone & Johnson, 2007). In a recent study, Taheri et al (2019) showed that these findings extend to the computing subdiscipline as well. Historically, computing has had a sexist and racist culture (Dunbar-Hester, 2019) that can discourage Latinx students from recognizing themselves or being accepted as the kind of individuals who engage with computing.…”
mentioning
confidence: 83%
“…Previous scholarship has demonstrated that the development of a strong STEM identity positively impacts STEM persistence and intention to persist (e.g., Brickhouse et al, 2000; Carlone & Johnson, 2007). In a recent study, Taheri et al (2019) showed that these findings extend to the computing subdiscipline as well. Historically, computing has had a sexist and racist culture (Dunbar-Hester, 2019) that can discourage Latinx students from recognizing themselves or being accepted as the kind of individuals who engage with computing.…”
mentioning
confidence: 83%
“…Scholars have only recently investigated the unique traits of computing identity (Taheri et al, 2018(Taheri et al, , 2019. Computing identity, or how one feels like a "computing person," is strongly associated with fostering persistence in undergraduate computing (Taheri et al, 2019) and computing career choice (Mahadeo et al, 2020). Yet, less is known about how mentors contribute to computing identity development, especially compared to research on mentorship and science identity (e.g., Chemers et al, 2011;Robnett et al, 2018).…”
Section: Psychosocial Outcomes Of Mentorship In Computingmentioning
confidence: 99%
“…Scholars have only recently investigated the unique traits of computing identity (Taheri et al, 2018(Taheri et al, , 2019. Computing identity, or how one feels like a "computing person," is strongly associated with fostering persistence in undergraduate computing (Taheri et al, 2019) and computing career choice (Mahadeo et al, 2020).…”
Section: Psychosocial Outcomes Of Mentorship In Computingmentioning
confidence: 99%
“…Computing identity is considered a form of disciplinary identity [24]. The four sub-constructs that researchers use to describe computing identity include: 1) Interest; 2) Sense of Belonging; 3) Recognition; and 4) Competence/Performance [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1: Computing identity framework, adapted from [26] We define interest as the extent to which a student desires to actively engage with a computing subject area, including their willingness to explore and learn about topics related to the field [25,26]. Sense of Belonging encompasses all aspects of community spirit and support that students perceive to exist for themselves as they navigate their learning experiences in computing.…”
Section: Introductionmentioning
confidence: 99%